2021
DOI: 10.1038/s41401-021-00647-y
|View full text |Cite
|
Sign up to set email alerts
|

The glycolytic process in endothelial cells and its implications

Abstract: Endothelial cells play an obligatory role in regulating local vascular tone and maintaining homeostasis in vascular biology. Cell metabolism, converting food to energy in organisms, is the primary self-sustaining mechanism for cell proliferation and reproduction, structure maintenance, and fight-or-flight responses to stimuli. Four major metabolic processes take place in the energy-producing process, including glycolysis, oxidative phosphorylation, glutamine metabolism, and fatty acid oxidation. Among them, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 130 publications
0
47
0
Order By: Relevance
“…In a second vascular-related module, we found that cathepsin D (CTSD), a lysosomal protease known to disrupt endothelial cell junctions and increase vasopermeability, was associated with a group of glycolytic metabolites including D-glucose, glycerol-3-phosphate, and lactic acid (Monickaraj et al, 2018). Notably, increased vascular permeability and glycolysis are known features of a pro-angiogenic state (Leung and Shi, 2021). Although dysregulated angiogenesis occurs in COVID-19 patients (Ackermann et al, 2020), how these events are coordinated remains poorly understood.…”
Section: Protein-metabolite Network Identify Potential Mediators Of C...mentioning
confidence: 99%
“…In a second vascular-related module, we found that cathepsin D (CTSD), a lysosomal protease known to disrupt endothelial cell junctions and increase vasopermeability, was associated with a group of glycolytic metabolites including D-glucose, glycerol-3-phosphate, and lactic acid (Monickaraj et al, 2018). Notably, increased vascular permeability and glycolysis are known features of a pro-angiogenic state (Leung and Shi, 2021). Although dysregulated angiogenesis occurs in COVID-19 patients (Ackermann et al, 2020), how these events are coordinated remains poorly understood.…”
Section: Protein-metabolite Network Identify Potential Mediators Of C...mentioning
confidence: 99%
“…Due to the strategic positioning of the endothelium, ECs have earned a front-row seat to interact with blood, the largest source of oxygen and nutrients in the body [107]. From a metabolic viewpoint, ECs are largely glycolytic [54,106,108,109], that is, they do not take advantage of this ready-to-use bulk of oxygen to fuel the Krebs' cycle and oxidative phosphorylation (OXPHOS). In fact, ECs retrieve more than 85% of their energetic needs from glycolysis, while only a small amount of pyruvate generated during this process is used to fuel OXPHOS, whose rate has been estimated to be about 200-fold lower than glycolysis in human umbilical vein ECs (HUVECs) [54,106].…”
Section: Metabolic State Of the Endothelial Cell In The Adult Vascula...mentioning
confidence: 99%
“…In response to stressors, cells undergo senescence, a state of proliferation arrest and active metabolism fueled primarily by glycolysis-derived lactate (Wiley and Campisi, 2016). Interestingly, under normal circumstances, ECs obtain over 80% of adenosine triphosphate (ATP) from lactate despite oxygen availability (Warburg effect), probably explaining the SARS-CoV-2 predilection for these cells (Sabbatinelli et al, 2019;Leung and Shi, 2021). Indeed, as senescent ECs upregulate lactate even more than their younger counterparts, they engender an optimal environment for viral replication (Schmid et al, 2007;Wong et al, 2017).…”
Section: Sigma-1receptors and Ptsdmentioning
confidence: 99%